Interpretation of Gas Seepage on Seismic Data: Example from Malaysian Offshore - S.N Fathiyah Jamaludin, Abdul Halim Abdul Latiff, Askury A. Kadi, . (2016)
Gas seepage is one of the geological hazard in the subsurface exploration. Migration of gas usually originated from the deeper reservoir due to poor sealing properties of the cap-rock as well as existence of faults or fractures within the reservoir. In order for us to get familiar with the existence of gas seepage on seismic data, we need to know their characteristics and how do they look like.